Factor V Leiden and genetic defects of thrombophilia in childhood porencephaly. Issue 2 (1st March 1998) - Debus, Otfried; Koch, Hans Georg; Kurlemann, Gerhard; Sträter, Ronald; Vielhaber, Heinrich; Weber, Peter; Nowak-Göttl, Ulrike
Abstract : AIMS: To determine to what extent the Arg 506 to Gln point mutation in the factor V gene and further genetic factors of thrombophilia affect the risk of porencephaly in neonates and infants. METHODS: The Arg 506 to Gln mutation, factor V, protein C, protein S, antithrombin, antiphospholipid antibodies and lipoprotein (a) (Lp(a)) were retrospectively measured in neonates and children with porencephaly (n=24). RESULTS: Genetic risk factors for thrombophilia were diagnosed in 16 of these 24 patients: heterozygous factor V Leiden (n=3); protein C deficiency type I (n=6); increased Lp (a) (n=3); and protein S type I deficiency (n=1). Three of the 16 infants had two genetic risk factors of thrombophilia: factor V Leiden mutation combined with increased familial Lp (a) was found in two, and factor V Leiden mutation with protein S deficiency type I in one. CONCLUSIONS: The findings indicate that deficiencies in the protein C anticoagulant pathway have an important role in the aetiology of congenital porencephaly.